Enroute sustainability: metal free C–H bond functionalisation. (16th March 2023) - Roy, Sayan; Panja, Subir; Sahoo, Sumeet Ranjan; Chatterjee, Sagnik; Maiti, Debabrata
Abstract : The metal-free C–H functionalisation is providing environmentally benign, cost-effective, sustainable catalytic systems. Comprehensive developments of various metal-free C–H functionalisation reactions are the focal point of this review. Abstract : The term "C–H functionalisation" incorporates C–H activation followed by its transformation. In a single line, this can be defined as the conversion of carbon–hydrogen bonds into carbon–carbon or carbon–heteroatom bonds. The catalytic functionalisation of C–H bonds using transition metals has emerged as an atom-economical technique to engender new bonds without activated precursors which can be considered as a major drawback while attempting large-scale synthesis. Replacing the transition-metal-catalysed approach with a metal-free strategy significantly offers an alternative route that is not only inexpensive but also environmentally benign to functionalize C–H bonds. Recently metal free synthetic approaches have been flourishing to functionalize C–H bonds, motivated by the search for greener, cost-effective, and non-toxic catalysts. In this review, we will highlight the comprehensive and up-to-date discussion on recent examples of ground-breaking research on green and sustainable metal-free C–H bond functionalisation.